Analisis Nilai Sosial dan Nilai Moral dalam Novel â€œMenikah dengan Calon Mertuaâ€ di Aplikasi Noveltoon - RM. Joko Priono; RB. Hendri Kuswantoro; Adi Sucipto (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this study is to describe the sosial values and moral values contained in the novel Marrying The Future In-Laws by Sugar Glider. The research method used in studying sugar Glider's novel MarryIng The Future In-Laws is a descriptive qualitative method. The object of this study is sosial values and moral values in the novel MarryIng The Future In-Laws by Sugar Glider which is presented through the Noveltoon application. The data collection technique in this study used a literature study technique. The stages carried out in this study include the stages of data acquisition, data collection and determination of units of analysis. Next is the stage of data selection, as well as a test of the validity of the data. The last stage is the process of analyzing and presenting data. The results of the research and discussion found that the story in sugar Glider's novel Marrying The Future Father-in-Law has things related to sosial and moral values. The sosial and moral values contained in each episode consist of man's relationship with God, man's relationship with himself, man's relationship with sesame and man's relationship with his environment. The sosial and moral values that emerge are more towards values that are considered good and values that are considered bad by society through the stories of their characters in each episode while directing the reader to be able to identify the good and bad values sosially and morally. Sosial values and moral values in the novel Marrying The Future In-Laws can be used as an alternative learning material for prose studies in the scriptwriting course of students of the Multi Media High School Game Technology Study Program.